TP53 mutation variant allele frequency is a potential predictor for clinical outcome of patients with lower-risk myelodysplastic syndromes - Belickova, Monika; Vesela, Jitka; Jonasova, Anna; Pejsova, Barbora; Votavova, Hana; Merkerova, Michaela Dostalova; Zemanova, Zuzana; Brezinova, Jana; Mikulenkova, Dana; Lauermannova, Marie; Valka, Jan; Michalova, Kyra; et al. (Oncotarget, 2016)
TP53 mutations are frequently detected in patients with higher-risk myelodysplastic syndromes (MDS); however, the clinical impact of these mutations on the disease course of patients with lower-risk MDS is unclear. In this study of 154 lower-risk MDS patients, TP53 mutations were identified in 13% of patients, with prevalence in patients with del(5q) (23.6%) compared to non-del(5q) (3.8%). Two-thirds of the mutations were detected at the time of diagnosis, and one-third were detected during the course of the disease. Multivariate analysis demonstrated that a TP53 mutation was the strongest independent prognostic factor for overall survival (OS) (HR: 4.39) and progression-free survival (PFS) (HR: 3.74). Evaluation of OS determined a TP53 variant allele frequency (VAF) threshold of 6% as an optimal cut-off for patient stratification. The median OS was 43.5 months in patients with mutations detected at the time of diagnosis and a mutational burden of > 6% VAF compared to 138 months (HR 12.2; p = 0.003) in patients without mutations; similarly, the median PFS was 20.2 months versus 116.6 months (HR 79.5; p < 0.0001). In contrast, patients with a mutational burden of < 6% VAF were stable for long periods without progression and had no significant impact on PFS or OS. Additionally, we found a high correlation in the mutational data from cells of the peripheral blood and those of the bone marrow, indicating that peripheral blood is a reliable source for mutation monitoring. Our results indicate that the clinical impact of TP53 mutations in lower-risk MDS patients depends on the level of mutational burden.
Keywords: TP53; dospělí; Multivariate Analysis; Prognosis; prognosis; senioři nad 80 let; alely; Humans; Mutation; lidé středního věku; myelodysplastické syndromy; Gene Frequency; Middle Aged; Aged, 80 and over; Young Adult; Kaplanův-Meierův odhad; mladý dospělý; prognóza; Risk Factors; Myelodysplastic Syndromes; mužské pohlaví; Tumor Suppressor Protein p53; Adult; nádorový supresorový protein p53; rizikové faktory; Chromosomes, Human, Pair 5; frekvence genu; multivariační analýza; ženské pohlaví; Female; chromozomální delece; lidské chromozomy, pár 5; mutational status; lidé; mutace; Aged; senioři; Male; variant allele frequency; Chromosome Deletion; myelodysplastic syndrome; Kaplan-Meier Estimate; Alleles